Strategy to Increase Tourism and Economic Growth in West Java - Mulyadi, Tirta (Yayasan Pendidikan Belajar Berdikari, 2024)
Three forces are constantly in charge of expanding output: capital growth, improvements in technology, and an increase in the number and quality of labour. Due to its multisectoral nature, tourism is today a viable alternative industry for economic growth in developing nations like Indonesia. The purpose of this study is to determine the relationship between the gross domestic product (GRDP) and the number of workers, tourists, and gross value added in the West Java Province. Five West Javan districts were included in the panel data study, which covered the years 2013–2023